Methodological aspects in ruminal digestion studies. II. Effect of the dietary roughage - Paz, Manuel Enrique Ruiz (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was conducted to examine the effect of two different tropical grasses (sugarcane tops and elephant grass), fed to a rumen-fistulated steer, upon the in situ digestion of eight types of pigeon pea forage. In one experimental period, the animals were fed sugarcane tops supplemented with pigeon pea forage and sorghum grain (2.2, 0.5 and 0.4 kg DM/100 kg LW/day, respectively). In a second period, elephant grass was substituted for the sugarcane tops. The pigeon pea forage samples were dried, ground to 1 mm size particles and placed in nylon bags (3 bags per sample) which were incubated in the rumen during 48 h. The disappearance of dry matter was calculated as the in situ digestibility of the sample. The statistical analysis revealed a highly significant effect (P < 0.03) of the roughage fed upon the in situ digestibility of the pigeon pea forages. When the elephant grass ration was fed, the average in situ digestibility of pigeon pea dry matter was 42.3 ± 2.10%; with sugarcane tops, the digestibility averaged 38.4 ± 3.38%. Based on this result and in view of the literature it is concluded that a supplementary legume not only has a positive effect on the digestion of poor roughages but these, in turn, affect the digestibility of the legume. Thus, it is important to take this into account in digestion studies, especially those designed for the nutritional characterization of feeds.